Modern Asian theatre and performance 1900-2000 - Wetmore, Kevin J. Jr. 1969-; Liu, Siyuan 1964 November 7-; Mee, Erin B. (London Bloomsbury, 2014)
Modern Asian Theatre and Performance 1900-2000 is a ground-breaking survey, tracking the advent of modern drama in Japan, India, China, Korea and Southeast Asia. It considers the shaping power of realism and naturalism, the influence of Western culture, the relationship between theatrical modernisation and social modernisation, the links between so-called traditional and modern theatrical practices, the importance of hybridity in the development of modern drama, and how theatre operates in contemporary Asian society.--from back cover.
Modern Japanese theatre through the Occupation -- Modern Japanese theatre: 1960 through the millennium -- Modern Chinese theatre to 1949 -- Modern Chinese theatre after 1949 -- Chinese drama outside the mainland: Taiwan and Hong Kong -- Modern Korean theatre -- Modern Indian theatre -- Theatre of roots: Post-independence theatre in India -- Modern southeast asian drama.
Includes bibliographical references (pages 284-294) and index.
Keywords: Theater -- Asia -- History